2021
DOI: 10.3390/vaccines10010023
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of COVID-19 Vaccines against Delta (B.1.617.2) Variant: A Systematic Review and Meta-Analysis of Clinical Studies

Abstract: The high transmissibility, mortality, and morbidity rate of the SARS-CoV-2 Delta (B.1.617.2) variant have raised concerns regarding vaccine effectiveness (VE). To address this issue, all publications relevant to the effectiveness of vaccines against the Delta variant were searched in the Web of Science, Scopus, EMBASE, and Medline (via PubMed) databases up to 15 October 2021. A total of 15 studies (36 datasets) were included in the meta-analysis. After the first dose, the VE against the Delta variant for each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
36
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 48 publications
4
36
0
1
Order By: Relevance
“…The VE against severe disease requiring hospitalization was quite high, even when the delta variant was dominant. The adjusted VE against COVID-19-related hospitalization was 98% (95% CI: 85–99%) in our study ( Table S1 ), which is similar to the pooled VE against severe outcomes after two doses reported in a recent meta-analysis of 98.5% (95% CI: 95–99%) [ 29 ]. These results suggest that the mRNA vaccines help prevent severe COVID-19 breakthrough infection.…”
Section: Discussionsupporting
confidence: 89%
“…The VE against severe disease requiring hospitalization was quite high, even when the delta variant was dominant. The adjusted VE against COVID-19-related hospitalization was 98% (95% CI: 85–99%) in our study ( Table S1 ), which is similar to the pooled VE against severe outcomes after two doses reported in a recent meta-analysis of 98.5% (95% CI: 95–99%) [ 29 ]. These results suggest that the mRNA vaccines help prevent severe COVID-19 breakthrough infection.…”
Section: Discussionsupporting
confidence: 89%
“…To our knowledge, there are some studies evaluating the VE of COVID-19 vaccines against VOC [ 20 23 ]. Some relevant systematic review or meta-analysis about COVID-19 vaccines against Delta variant have been published to date [ 24 26 ], which did not include many recent studies as the most recent retrieval date was October 2021. Therefore, to gain insight in the VE of COVID-19 vaccines against five kinds of VOC, we conducted a comprehensive systematic review and meta-analysis including both RCTs and observational studies.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, B.1.617.2 (delta) and B.1.1.529 (omicron), the highly transmissible SARS-CoV-2 variants of concern, have brought new waves of infection worldwide and have accounted for breakthrough infections owing to their reduced sensitivity to the currently available vaccines. 17 Although vaccine effectiveness has been reported in real-world studies, 18 clinical efficacy against the prevalent delta variant of concern has been reported for only two vaccines in two randomized, controlled phase 3 trials. In one trial, the BBV152 vaccine (Bharat Biotech International) was shown to have an efficacy of 65.2%, 5 and in another, the SCB-2019 vaccine was shown to have an efficacy of 78.7%.…”
mentioning
confidence: 99%